Analisis Yuridis Putusan Bebas dalam Perkara Tindak Pidana Pembunuhan Berencana Secara Bersama-Sama (Studi Putusan Nomor 939 K/PID/2022) - Ciang, Zainul Duk; Nur, Fuad (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes an acquittal in a case of premeditated murder committed jointly by multiple perpetrators, focusing on Supreme Court Decision Number 939 K/PID/2022. Premeditated murder, as regulated under Article 340 of the Indonesian Criminal Code (Law No. 1 of 1946), requires elements of intent and prior planning, and may be committed jointly through the mechanism of complicity (deelneming) as provided in Article 55 paragraph (1) of the Criminal Code. This study employs a normative legal research method using statutory, conceptual, and case approaches, with primary data derived from statutory regulations and secondary data derived from books, legal documents, and journals. The findings show that the majority of the panel of judges applied the defense of necessity (noodweer) based on the concept of a "continuing event" to justify the defendant’s actions, despite facts indicating that the victims were already under the control of law enforcement officers and no longer armed, meaning the actual threat had ceased. This condition raises debate regarding the limits of applying the principles of proportionality and subsidiarity in the defense of necessity under Article 49 paragraph (1) of the Criminal Code. The study concludes that evidence constitutes a fundamental element in determining criminal liability, and that the dissenting opinion in the decision is considered to better reflect legal certainty, proportionality, and the protection of human rights compared to the majority judges’ considerations.